Identifying Significant Factors Associated with Career Selection: A survey based study in Pakistan (Pakistan Journal of Engineering, Technology and Science, 2024)
To best utilize the talent of students, they should be provided appropriate guidance in selecting their careers. In this paper, we explore and verify significant factors associated with an appropriate career selection that can lead to success. We consider three broad categories of factors: educational interests and problems, environmental issues and family background.  Among these broader categories, we identify seven significant factors important for appropriate career selection of students. These include parents’ professions, financial problems, favorite subjects in high school, availability of educational facilities, economic circumstances and parents’ influence. We also study the relation between professional degree and its relevancy to a profession. Based on a sample (n=228), we find that in Pakistan, around 71% professionals adopt professions relevant to their professional degrees, whereas 29% professionals either do partially relevant jobs or join some completely irrelevant professions. Results suggest that for a successful career, students should study the subject most suited to their interests and pursue careers relevant to their professional degrees.
Keywords: Career selection; Decision making; influencing factors; factor analysis; professionals; educational data mining